A pectin from fruits of Lycium barbarum L. decreases β-amyloid peptide production through modulating APP processing. (1st December 2018) - Zhou, Lishuang; Liao, Wenfeng; Zeng, Hui; Yao, Yanli; Chen, Xia; Ding, Kan
Highlights: The structure of a pectin polysaccharide LBP1C-2 was characterized. The backbone of the polysaccharide LBP1C-2 was alternate 1, 4-α-Gal p A and 1, 2-α-Rha p . LBP1C-2 inhibited Aβ42 production in a dose-dependent manner with no cytotoxicity. LBP1C-2 decreases Aβ42 production through mediating BACE1 and ADAM10 as well as IDE expression. Abstract: Here, a pectin LBP1C-2 with the molecular weight of 99.8 kDa was purified from fruits of Lycium barbarum L. Its structure was elucidated as a backbone of alternate 1, 2-linked α-Rha p and 1, 4-linked α-Gal p A, with branches of terminal (T) -, 1, 3-, 1, 6- and 1, 3, 6-linked β-Gal p, T-, 1, 5- and 1, 3, 5-linked α-Ara f and T-linked β-Rha p substituted at C-4 of 1, 2, 4-linked α-Rha p . The cell-based experiments indicated that LBP1C-2 suppressed Aβ42 production in a dose-dependent manner with no cytotoxicity. Further study showed that expression of β-site APP cleaving enzyme 1 (BACE1) was attenuated by LBP1C-2, while expression of ADAM10 was up-regulated by LBP1C-2. Moreover, LBP1C-2 promoted the expression of insulin-degradation enzyme (IDE). These results suggested that LBP1C-2 might be a leading compound for anti-Alzheimer's disease therapy by decreasing Aβ42 production through mediating BACE1 and ADAM10 as well as IDE expression.